2007
DOI: 10.1111/j.1440-1681.2007.04690.x
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic Acid Receptors May Mediate the Analgesic Effects of Emulsified Halogenated Anaesthetics

Abstract: 1. The present study was designed to investigate the relationship between spinal cord alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors and the analgesic effects of emulsified halogenated anaesthetics. 2. After having established the mouse model of analgesia by intraperitoneal or subcutaneous injections of appropriate doses of emulsified enflurane, isoflurane or sevoflurane, we injected different doses of AMPA intrathecally and observed effects on the pain threshold using the hot-plate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(60 reference statements)
1
2
0
Order By: Relevance
“…Previous studies support the efficacy and safety of the iv administration of emulsified inhalation anesthetics in animals [34,35]. According to drug pharmacokinetics and our preliminary experiments [6,7], we confirmed that ip and sc injection of emulsified inhalation anesthetics can achieve hypnosis and analgesia similar to that produced by inhalation. In the hypnosis test, hypnotic doses of emulsified sevoflurane induced the loss of mouse righting reflex.…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies support the efficacy and safety of the iv administration of emulsified inhalation anesthetics in animals [34,35]. According to drug pharmacokinetics and our preliminary experiments [6,7], we confirmed that ip and sc injection of emulsified inhalation anesthetics can achieve hypnosis and analgesia similar to that produced by inhalation. In the hypnosis test, hypnotic doses of emulsified sevoflurane induced the loss of mouse righting reflex.…”
Section: Discussionsupporting
confidence: 80%
“…There is evidence that activation of NO synthase (NOS), with consequent production of NO, triggered by NMDA receptor activation plays an important role in central and peripheral modulation of nociception 8 . Because isoflurane is certainly able to act as an antagonist at spinal NMDA receptors to produce antinociception, 9,10 it is possible that it may influence NO production. If the NMDA receptors that are blocked by isoflurane are also linked to NO synthesis and release, then it is reasonable to predict that pretreatment with intrathecal injection of the NO precursor l ‐arginine would reduce the antinociceptive effects produced by isoflurane.…”
Section: Introductionmentioning
confidence: 99%
“…Various in vitro studies have found that the enhancement of inhibitory neurotransmitter function and inhibition of excitatory neurotransmitter function to be plausible mechanisms underlying the action of inhalation anesthetics. Analgesic effects of anesthetics may be related to alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor [4,5,6], benzodiazepine receptor [7], N-methyl-D-Aspartate receptor [8,9,10], glycine receptor [11,12,13,14], nerve nicotinic receptors [15], and alpha 2 receptors [16] on the spinal cord. Morphological and molecular biology research has indicated that the 5-serotonin receptor 1A (5-HT 1A R) is widely distributed in the nervous system.…”
mentioning
confidence: 99%